2007
DOI: 10.1007/s10546-007-9158-9
|View full text |Cite
|
Sign up to set email alerts
|

Modelling dust distributions in the atmospheric boundary layer on Mars

Abstract: A time and height dependent eddy diffusion model is used to investigate possible scenarios for the size distribution of dust in the lower atmosphere of Mars. The dust is assumed to either have been advected from a distant source or to have originated locally. In the former case, the atmosphere is assumed to initially contain dust particles with sizes following a modified gamma distribution. Larger particles are deposited relatively rapidly while small particles are well mixed up to the maximum height of the af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
0
18
1
Order By: Relevance
“…As a result, models of the Martian boundary layer will play an important role in data assimilation and interpretation as they have for Viking and Pathfinder [ Savijärvi , 1999]. Taylor et al [2007] present some model results on dust distributions within the boundary layer for 70°N, while other coupled boundary layer and dust modeling and large eddy simulation studies are ongoing. Mars global circulation models [e.g., Moudden and McConnell , 2005] and model databases [ Lewis et al , 1999] have been used to help in the determination of the meteorological conditions we expect to find at the Phoenix site.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, models of the Martian boundary layer will play an important role in data assimilation and interpretation as they have for Viking and Pathfinder [ Savijärvi , 1999]. Taylor et al [2007] present some model results on dust distributions within the boundary layer for 70°N, while other coupled boundary layer and dust modeling and large eddy simulation studies are ongoing. Mars global circulation models [e.g., Moudden and McConnell , 2005] and model databases [ Lewis et al , 1999] have been used to help in the determination of the meteorological conditions we expect to find at the Phoenix site.…”
Section: Discussionmentioning
confidence: 99%
“…The opacity as a function of the volumetric number density, N v , is [e.g., Taylor et al , 2007] In , Q ext can be treated as a function of the integrated dust size distribution rather than radius and can be extracted from the integral along with π and N v , such that The value of Q ext used by the retrieval algorithm is 0.35, which is obtained from Mie theory as described by Kleinböhl et al [2009a].…”
Section: Data and Basic Analysismentioning
confidence: 99%
“… Conrath [1975] attributed the vertical distribution to the competing effects of sedimentation and vertically uniform vertical eddy diffusion. This simple picture has been complicated by (1) the possibility of additional removal processes such as the enhancement of sedimentation by the condensation of volatiles on dust particles [ Nelli and Murphy , 2002]; (2) modeling of vertical transport above the boundary layer due to dynamical processes such as the thermal tides [ Wilson and Hamilton , 1996]; (3) more detailed treatment of mixing within the boundary layer [ Taylor et al , 2007]; (4) explicit consideration in models of dust particle size and its variability [ Kahre et al , 2008]; and (5) consideration of the sources of dust such as mountain slope circulations [ Lee et al , 1982; Rafkin et al , 2002] and dry convective vortices (“dust devils”) [ Kahre et al , 2006; Cantor et al , 2006; Greeley et al , 2006]. Of these processes, dust devils have been the principal focus of investigation.…”
Section: Introductionmentioning
confidence: 99%
“…T07 showed that we can expect a rapid decrease in particle concentration with height at the afternoon boundary layer height in cases without a local source of particles. However, the use of a closed PBL diurnal cycle meant that their model is insufficient to make quantitative comparisons with Phoenix lander data.…”
Section: Introductionmentioning
confidence: 99%